2012
DOI: 10.1111/j.1474-9726.2012.00863.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced repression of cytokine signaling ameliorates age‐induced decline in hematopoietic stem cell function

Abstract: SummaryAging causes profound effects on the hematopoietic stem cell (HSC) pool, including an altered output of mature progeny and enhanced self-propagation of repopulating-defective HSCs. An important outstanding question is whether HSCs can be protected from aging. The signal adaptor protein LNK negatively regulates hematopoiesis at several cellular stages. It has remained unclear how the enhanced sensitivity to cytokine signaling caused by LNK deficiency affects hematopoiesis upon aging. Our findings demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…For example, enhanced cytokine signaling can counteract age-related HSC functional decline in the setting of loss of lymphocyte-specific adapter protein (LNK) deficiency in stem cells [53 ▪ ], whereas in the absence of the GAP junction formed by Connexin 43, HSCs are defective in unloading their reactive oxygen species onto niche cells and maintaining proper homeostasis under stress [54]. It is an intriguing possibility that niche factors might influence aging and clonality of HSCs and aging-associated progression of leukemia [54,55 ▪ ].…”
Section: Aging Of Hematopoietic Stem Cellsmentioning
confidence: 99%
“…For example, enhanced cytokine signaling can counteract age-related HSC functional decline in the setting of loss of lymphocyte-specific adapter protein (LNK) deficiency in stem cells [53 ▪ ], whereas in the absence of the GAP junction formed by Connexin 43, HSCs are defective in unloading their reactive oxygen species onto niche cells and maintaining proper homeostasis under stress [54]. It is an intriguing possibility that niche factors might influence aging and clonality of HSCs and aging-associated progression of leukemia [54,55 ▪ ].…”
Section: Aging Of Hematopoietic Stem Cellsmentioning
confidence: 99%
“…[14][15][16] Affymetrix gene expression analysis RNA was extracted from 10 000 sorted HSCs (Lin -Sca1 1 c-Kit…”
Section: Telomere Length Measurementmentioning
confidence: 99%
“…Perhaps supporting this interpretation, the demonstration of increased levels of the inflammatory cytokine Rantes in the aging BM microenvironment was suggested to contribute to the age‐associated myeloid skewing [92]. In addition, we and others have found that the lack of the adaptor protein Lnk, which functions to dampen extrinsic cytokine signals, abrogates the phenotypes associated with HSC aging [93, 94]. Young as well as aged Lnk −/− mice display an expanded HSC pool.…”
Section: Is the Hsc Aging State Reversible?mentioning
confidence: 76%
“…Young as well as aged Lnk −/− mice display an expanded HSC pool. However, aged Lnk −/− HSCs harbored superior reconstitution potential compared with aged WT HSCs, with maintenance of a robust lymphoid differentiation potential [93, 94]. Recently, prolonged fasting was suggested to dampen the consequence of age on HSC function through normalization of the clonal distribution of the aging HSC compartment, that is, by reducing the frequency of myeloid‐biased HSCs and increasing the frequency of lymphoid‐biased HSCs [95].…”
Section: Is the Hsc Aging State Reversible?mentioning
confidence: 99%